ENT 530 Social Media Portfolio: Batik Bitez / Muhammad Iskandar Dzulkarnain Mohd Zaidi - Mohd Zaidi, Muhammad Iskandar Dzulkarnain (2021)
Batik Bitez is a dessert shop of food services bussiness. The main objectives of this bussiness is to achieve a bussiness online to offer a variety of Batik Bitez to our customer and client with affordable price and special variety of flavour taste from the best ingredients maker in Malaysia . My bussiness was started on 21 November 2020. The achievement of this bussiness have been review by the customer and client because of the taste, uniqueness and differencess from current product. This bussiness receiving a lot of liked and review due to the cheap and affordable price. Thus, this product provides a good insight for the countinuous sales to our customer and client. Therefore, Batik Bitez is a good choice and can be a top of market list to futher expanded into many different areas during this Movement Control Order (MCO).